Health warning labelling practices on narghile (shisha, hookah) waterpipe tobacco products and related accessories. Issue 3 (25th May 2010) - Nakkash, Rima; Khalil, Joanna
Abstract : Background: Waterpipe tobacco smoking prevalence is increasing around the globe despite current evidence that smoke emissions are toxic and contain carcinogenic compounds. Objective: To evaluate current health warning labelling practices on waterpipe tobacco products and related accessories. Methods: All waterpipe tobacco products, as well as waterpipe accessories, were purchased from Lebanon and a convenience sample was obtained from Dubai (United Arab Emirates), Palestine, Syria, Jordan, Bahrain, Canada, Germany and South Africa. Findings: Of the total number of waterpipe tobacco products collected from Lebanon, the majority had textual health warning labels covering on average only 3.5% of total surface area of the package. Misleading descriptors were commonplace on waterpipe tobacco packages and related accessories. Conclusions: There are no WHO FCTC compliant waterpipe-specific health warning labels on waterpipe tobacco products and related accessories. Introducing health warnings on waterpipe tobacco products and accessories will probably have worldwide public health benefits.